Labile copper and zinc fractions under different salinity conditions in a shipyard area in the patos lagoon estuary, south of Brazil - Costa, Luiza Dy Fonseca (2013)
Copper and zinc are common elements in paint residues and can be toxic to estuarine organisms. This study aims to determine the labile dissolved and labile particulate fractions (LPFs) of copper and zinc in the estuarine waters of a shipyard in southern Brazil under different salinity levels and in different seasons. The labile dissolved fraction was determined using the diffusive gradient in thin-film (DGT) technique. The variations in DGT-Cu (0.22-1.05 µg L-1), DGT-Zn (0.54-18.39 µg L-1), LPF-Cu (1.22-3.77 µg g-1), and LPF-Zn (4.29-19.12 µg g-1) concentration were related to changes in their physico-chemical parameters and as a result of boat maintenance activities